Osteoarthritis of the hip: are degenerative tears of the acetabular labrum predictable from features on hip radiographs?. (May 2021) - Gonzalez, Felix M; Gagnon, Marie-Helene; Reiter, David; Younan, Yara; Sayyid, Samia; Singer, Adam; Umpierrez, Monica; Sharma, Gulshan B; Robertson, Douglas D
Background: A common feature of hip arthritis is the presence of labra tears. Recent literature suggests against the use of magnetic resonance imaging (MRI) in patients aged >45 years for the assessment of hip pain related to arthritis. Purpose: To determine if radiographic features of osteoarthritis detectable on routine hip radiographs are accurate and reliable surrogate markers of degenerative acetabular labral tears identified on MR arthrography (MRA) and corroborated during arthroscopy. Material and Methods: A retrospective study involving 86 symptomatic patients (hip pain) with radiologic work-up included MRA and pelvic or hip radiographs that underwent hip arthroscopy within three months. Imaging characteristics assessed on hip radiographs include measurements of superior acetabular, femoral head osteophyte, cortical thickness of the femoral shaft, and minimum joint space as well as presence of subchondral sclerosis of the femoral head and acetabulum, femoral shaft buttressing, and grade of arthritis. Presence of a labral tear was determined by consensus between three readers as well as by surgical correlation. The Pearson's chi-squared and Fisher's exact tests were used to compare presence of labral tears with each radiographic feature. Results: Seventy-one patients (82.6%) had labral tears: 49 (69%) women and 22 (31%) men. Receiver operating characteristic analysis showed statistical significance ( P <0.05) between presence of a labral tear and acetabular and femoral head osteophyte sizes but failed to demonstrate any significance regarding acetabular subchondral sclerosis, cortical thickness, buttressing, or minimum joint space. Conclusions: Radiographic markers such as the acetabular and femoral head osteophyte sizes demonstrated statistical significance with the presence of labral tears.